The Dragon's Prophecy: Israel, the Dark Resurrection, and the End of Days - Cahn, Jonathan ([Place of publication not identified] : Frontline, 2024)
"Is there more to the world than meets our eyes - another realm that's transforming our world at this very moment? Is there an ancient vision that unlocks what is really happening to our world and what is yet to come? A dangerous force from ancient times that is now operating in the world and determining the course of world events? Did a three-thousand-year old mystery actually foretell the invasion of Israel by Hamas down to the year - and even the exact date? Is there a secret to the Book of Revelation that actually reveals what is taking place right now?"--.
new book 2024 fall.
Keywords: End of the world; Christianity; Religious aspects; RELIGION / Christian Theology / Christology